Justification of Intensive care management of children with severe COVID19 (а case study) - Tkachuk, Roman; Koloskova , Olena; Garas , Mykola; Bilous , Tetyana; Gurina , Iryna; Polishchuk , Andii; Antoniichuk, Viktoriia (The Ukrainian Scientific Medical Youth Journal, 2024)
the unprecedented COVID-19 pandemic that spread across the world and lasted for more than 3 years had significant medical and social consequences. Despite the fact that in the children's population the coronavirus infection has a milder course and a much lower risk of mortality, there are individual cases with pre-existing comorbidities that cause severe acute respiratory distress syndrome. Thus, in most cases, severe COVID-19 developed in children with pre-existing conditions, including: immunodeficiency, diabetes mellitus, bronchial asthma, etc. Therefore, comorbidities disposed children to progress to severe Covid-19 which requires treatments with more aggressive therapeutic tactics and personalised management. The article presents a clinical case of severe acute respiratory distress syndrome caused by the SARS-CoV-2 virus in an early age child. The patient was observed in the Anesthesiology and Intensive Therapy Department of the Chernivtsi Regional Children's Clinical Hospital. Due to acute respiratory infection, the child has been developing signs of respiratory failure. The available instrumental findings confirmed right lung pneumonia, complicated by pneumothorax. Laboratory tests confirmed leukocytosis, thrombocytopenia, hypertransfusion, increased procalcitonin, increased level of C-reactive protein, D-dimer and interleukin-6 as well as circulating immune complexes. The treatment regimen included respiratory protection (oxygen therapy), support of hemodynamics (infusion of glucose-saline solutions), administration of intravenous normal human immunoglobulin, a short course of parenteral glucocorticosteroids, the use of step-by-step combined antibacterial therapy and a direct-acting antiviral drug (remdesivir), and thromboembolism prophylaxis (low-molecular-weight heparin). Following intensive treatment, the child's condition was characterised by a slow positive dynamics, leading to full recovery. This case demonstrates the need for timely detection of life-threatening conditions caused by COVID-19 and requires an aggressive management of child's condition using a complex intensive therapy.